1975
DOI: 10.1210/endo-97-4-825
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Human Endometrial Estradiol Dehydrogenase by Progestins

Abstract: Estradiol-17beta dehydrogenase activity in proliferative human endometrium (average of 1.5 nmole of estrone formed from estradiol/mg protein/h) was stimulated as much as as 6-fold during incubations of tissue slices in culture medium containing progesterone. Stimulation was already detectable at 7 h and the highest activity values were reached at 48-72 h of incubation in the presence of excess progesterone. Maximal stimulation was achieved with concentrations of the hormone of 0.25 mug/ml or higher. At concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
4

Year Published

1976
1976
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 297 publications
(77 citation statements)
references
References 0 publications
1
72
0
4
Order By: Relevance
“…This observation is supported by the comparison of the sedimentation patterns of nucleus-bound steroid hormone receptors from normal myometrium in the middle proliferative and early secretory phases and from leiomyoma, and by kinetics of steroid hormone transfer from the cytoplasm to the nucleus under equilibrium conditions. (29,30) and our group (10) on human endometrium have shown, is subject to the inductive effect of the progesterone receptor mechanism. One can only speculate on the cause and pathophysiological significance of the differences in progesterone receptor contents of normal myometrium and leiomyoma: Since, as animal experiments have shown, the progesterone receptor is induced via the estradiol receptor mechanism, and thus represents an end product of the chain of estradiol action, it can be inferred that an alteration at one of the steps sur> sequent to the translpeation of the estradiol receptor (transcription, processing, translation) leads to the "progesterone receptor defect".…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This observation is supported by the comparison of the sedimentation patterns of nucleus-bound steroid hormone receptors from normal myometrium in the middle proliferative and early secretory phases and from leiomyoma, and by kinetics of steroid hormone transfer from the cytoplasm to the nucleus under equilibrium conditions. (29,30) and our group (10) on human endometrium have shown, is subject to the inductive effect of the progesterone receptor mechanism. One can only speculate on the cause and pathophysiological significance of the differences in progesterone receptor contents of normal myometrium and leiomyoma: Since, as animal experiments have shown, the progesterone receptor is induced via the estradiol receptor mechanism, and thus represents an end product of the chain of estradiol action, it can be inferred that an alteration at one of the steps sur> sequent to the translpeation of the estradiol receptor (transcription, processing, translation) leads to the "progesterone receptor defect".…”
Section: Discussionmentioning
confidence: 90%
“…The result is that the estradiol receptor mechanism, which is responsible for both its own induction and that of the progesterone receptor, is blocked (10,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Although estrone is weakly estrogenic, it exhibits a lower binding affinity for ERs than estradiol, and it diffuses out of the cell more rapidly than estradiol. In the myometrium, the activity of this enzyme is maximal during the early secretory phase because of upregulation by progesterone (Tseng and Gurpide 1973), resulting in a diminished estradiol effect during the second half of the cycle. In leiomyomas, on the other hand, the reduced activity of 17β-hydroxysteroid dehydrogenase may allow for the accumulation of estradiol in the cells during the secretory as well as the proliferative phase of the cycle, thus resulting in continual stimulation by estrogen, with upregulation of both the ERs and PRs, accompanied by the associated growth-promoting effects.…”
Section: Review | Uterine Leiomyomamentioning
confidence: 99%
“…These may change the state of equilibrium between estradiol and estrone to some extent, though from studies on the human placental 17/J-hydroxysteroid dehydrogenase (24,25) it has been shown that under physiological conditions the equilibrium of the reaction lies on the side of estrone. Furthermore it has been shown by supervision experiments with human endometrium (20)(21)(22), that estrone (in contrast to estradiol) is not accumulated in the target cell. This observation seems all the more important since estrone is known to compete for specific estradiol receptor and enzyme binding-sites.…”
Section: Kinetic Analysesmentioning
confidence: 99%
“…an increase in enzyme activity is observed in vitro and in vivo after estrogen pretreatment followed by progesterone application (this can be blocked by inhibitors of protein synthesis); 2. there is a positive correlation between microsomal 17/J-hydroxysteroid dehydrogenase activity and progesterone receptor concentration; and 3. endometrial carcinomas only react to high-dose gestagen therapy with an increase in their 170-hydroxysteroid dehydrogenase activity if they possess adequate levels of progesterone receptors. For human myometrium there is less substantial evidence for a progesterone induced synthesis of the 17β-hydroxysteroid dehydrogenase than for human endometrium (20)(21)(22)(23). Other causes for a postovulatory increase of enzyme activity in human myometrium therefore have to be taken into consideration, such as intracellular proton concentration or the redox state…”
mentioning
confidence: 99%